Correlation Analysis of Radical Polymerization Reactor Operating Conditions to Industrial Scale Swelling Capacity of Superabsorbent - Willy Aulia Ilham; Teguh Kurniawan; Saepurahman Saepurahman; Ratna Sari Siti Aisyah (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2023)
Superabsorbent polymer (SAP) is a polymer that has many functions in modern human’s life, one of which is as an absorbent material in baby diapers. The growing demand for SAP with high quality SAP makes it necessary to study the effects of production variables on the quality of SAP on an industrial scale. The quality of SAP is determined by the number of Swelling Capacity (SC) where the ideal number is greater than 50 g/g. Many previous studies regarding the effect of synthesis parameters on the number of SC of SAP were limited to the laboratory scale where the polymerization conditions were different from the industrial scale. Also the number of variables and SC data obtained from laboratory scale synthesis were limited. The polymerization stage in the reactor with its accompanying operating variables such as reaction temperature, monomer concentration, retention time, crosslinker concentration, addition of nitrogen gas and initiator concentration affects the value of SC in the industrial-scale SAP production process. This study aims to analyse the correlation between the reactor operating conditions and the number of SAP SC obtained. Correlation data analysis was done using microsoft excel with Data Analysis toolpak/ python by utilizing production data with a total of 1,562 entries where the correlation between each variables was calculated using the Pearson’s correlation coefficient. Based on the analysis, it was obtained that the variables that had the strongest correlation with the SC were retention time and reaction temperature with correlation coefficient values of 0.31 and -0.26. The weakest correlation was obtained from the addition of nitrogen gas and an initiator with a value of -0.07 and -0.02. Positive values indicate a relationship that is directly proportional while negative values indicate an inverse relationship. Based on the correlation analyses and trends, the ideal polymerization conditions have been identified.